Teori-Teori Pertumbuhan dan Pembangunan Ekonomi - Indah Wahyu Prastiwi; Dinda Amalia; Siti Khairani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Economic development has a broader meaning and encompasses comprehensive changes in the economic structure of society. This development process is a transformation marked by structural changes, both in the foundation of economic activities and in the economic framework of the society in question. In economic theory, it is understood that economic growth and equity often conflict with each other. If the focus of development is directed towards economic growth, it will be high, but it will not be accompanied by income equity, resulting in an unequal income distribution. Conversely, if the emphasis is placed more on equity, income distribution may improve, but economic growth could be lower. Developed countries have adopted a strategy of Redistribution with Growth, which means they strive to promote economic growth while simultaneously redistributing income by focusing on development projects that are equity-oriented and create a significant number of jobs.